Effects of Exercise Training and Weight Loss on Plasma Fetuin-A Levels and Insulin Sensitivity in Overweight Older Men. (9th July 2017) - Blumenthal, Jacob B.; Gitterman, Anna; Ryan, Alice S.; Prior, Steven J.
Abstract : Aerobic exercise training and weight loss (AEX+WL) improves insulin sensitivity in overweight adults; however, the underlying pathways are incompletely understood. Fetuin-A, a hepatokine that inhibits insulin signaling, may be involved in the salutary effects of AEX+WL. Therefore, we examined the effects of 6-month AEX+WL on plasma fetuin-A levels (36–48 hours after the last bout of exercise), aerobic capacity (VO2max ), body composition, glucose tolerance, and insulin sensitivity (M) in 16 sedentary, overweight-obese older men (age = 60 ± 2 years, BMI = 31 ± 1 kg/m 2 ) with no history of cardiovascular disease or diabetes. At baseline, fetuin-A levels correlated directly with adiposity and had a borderline inverse correlation with M. After AEX+WL, body weight decreased by 10 kg, while both VO2max and M increased by 16% (P < 0.005 for all). Contrary to our hypothesis, plasma fetuin-A levels increased after AEX+WL (1.16 ± 0.10 g/L versus 1.70 ± 0.19 g/L, P = 0.006 ). This increase was unrelated to changes in body composition or glucose metabolism, but directly correlated with changes in VO2max (r = 0.57, P < 0.05 ). Thus, in overweight-to-obese older men, AEX+WL appears to increase plasma fetuin-A levels. Although not associated with improvements in insulin sensitivity, this increase in fetuin-A was related to improvements in aerobic capacity and could be representative of the cardioprotective effects of AEX+WL in older men.